EFEK KOMBINASI DOSIS PUPUK N P K DAN CARA PEMUPUKAN TERHADAP PERTUMBUHAN DAN HASIL JAGUNG MANIS - Jumini Jumini; Nurhayati Nurhayati; Murzani Murzani (Jurnal Floratek, 2011)
This study was aimed at determining effects of combinations of doses N, P and K and fertilizer placement on growth and yield of sweet corn and also finding out interactions between the two treatments. The research was conducted at the Seed Garden of Agriculture Faculty, Unsyiah, using a factorial randomized complete block design. Factor studied were combinations of fertilizer doses of N, P and K (Urea, TSP and KCl), consisting of three levels: P1 = 400 + 250 + 200 kg/ha, P2 = 450 + 300 + 250 kg/ha, and P3 = 500 + 350 + 300 kg/ha, and fertilization manners, consisting of two levels: circle and sideband. The results showed that the combination of doses of fertilizer N, P and K exerted a highly significant effect on ear weight, cob weight and cob weight/ha and exerted a significant effect on plant height of 30 and 45 days after planting and  cob length, but did not affect cob diameter.  The best growth and yield was obtained in a combination of N, P and K 500 + 350 + 300 kg/ha. Fertilizer placement did not significantly affect plant growth and yield of sweet corn. There was no significant interaction between fertilizer dose combinations of N, P and K and fertilizer placement on growth and yield of sweet corn.